THE INFLUENCE OF ROLE PLAYS AND LEARNING MOTIVATION TOWARDS THE FIRST YEAR ROOM DIVISION STUDENTS’ SPEAKING ABILITY AT TOURISM POLYTECHNIC OF PALEMBANG - Indah Wati (ELTE Journal (English Languange Teaching and Education), 2019)
AbstractThis study is concerned withthe influence of Role plays and Learning Motivation towards the first year Room Division students’ Speaking Ability at Tourism Polytechnic of Palembang. In this study, 32 students of first year room division department were chosen as samples by means of two stages random sampling. This study applied factorial design. The data were collected by using questionnairres and speaking test. The data were analyzed by using Paired Sample T-test, Independent Sample T-test, and Two-Ways Anova. The result showed that first, there was significant influence of Role Play towards the first year room division students’ speaking ability. Second, there was significant influence of conventional teaching technique towards the first year room division students’ speaking ability. Third, there was significant influence of role play and conventional teaching technique towards the first year room division students’ speaking ability between students who have high and low learning motivation at Palembang Tourism Polytechnic. Fourth, there was interaction effect of role play and learning motivation towards the first year room division students’ speaking ability. It can be concluded that Role Play technique was quite effective to improve students’ speaking achievement.Keywords: Role Plays, Learning Motivation, Speaking Ability